2005
DOI: 10.1055/s-2005-916682
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Platelet Reactivity Index by Grotemeyer, Platelet Function Analyzer, and Retention Test Homburg To Monitor Therapy with Antiplatelet Drugs

Abstract: In 1974, Wu and Hoak described a method for determining circulating platelet aggregates. This method was modified by Grotemeyer in 1983. The platelet reactivity index (PR) is based on the ratio of platelet aggregates in blood samples obtained in different buffer solutions. Platelet aggregates are resolved when blood is sampled in EDTA-buffer, but remain fixed when EDTA-formalin-buffer is used. Generally, the PR is preferred, because in vitro manipulations of platelets are not necessary, and the results are cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 11 publications
(26 reference statements)
0
11
1
Order By: Relevance
“…It is used for quantitative determination of circulating platelet aggregates in vivo and for calculating platelet aggregation ratio (PAR). PAR values and its derivates have been used successfully to identify the effectiveness of antiplatelet drugs and their optimum dosage in patients suffering from stroke [1,7,8,9, 17, 18]. However, we failed to find any study using PAR as a predictive factor in differential diagnosis of ischemic cerebrovascular diseases.…”
Section: Introductioncontrasting
confidence: 41%
See 3 more Smart Citations
“…It is used for quantitative determination of circulating platelet aggregates in vivo and for calculating platelet aggregation ratio (PAR). PAR values and its derivates have been used successfully to identify the effectiveness of antiplatelet drugs and their optimum dosage in patients suffering from stroke [1,7,8,9, 17, 18]. However, we failed to find any study using PAR as a predictive factor in differential diagnosis of ischemic cerebrovascular diseases.…”
Section: Introductioncontrasting
confidence: 41%
“…The automatic coulter counters can be found in most hospitals. Koscielny et al [8] reported that PAR values could be correlated with values received from the retention test Homburg (RT-H) and the platelet function analyzer (PFA-100).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spontaneous hyperaggregability of platelets is described to be a risk factor for major adverse cardiovascular events and occlusion syndromes [1,2,15,28,38]. On the other hand, there are a lot of diseases associated with non-functional or partly non-functional platelets, which need to be tested using different activators (adenosine 5 -diphosphate, arachidonic acid, thrombin, collagen, ristocetin, etc.)…”
Section: Introductionmentioning
confidence: 99%